CLINICAL CASE OF CHRONOTHERAPY OF ARTERIAL HYPERTENSION - Petrenko, O. V.; Bogun, L. V.; Yabluchansky, M. I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
A clinical case of chronotherapy of arterial hypertension is described. In patient U., according to ambulatory blood pressure monitoring (ABPM) results, 24-h average value was 145 mmHg for systolic blood pressure (SBP) and 88 mmHg for diastolic blood pressure (DBP), DBP circadian rhythm had «over dipper» pattern while SBP circadian rhythm was normal. Taking into account the daily individual BP profile the patient was prescribed antihypertensive drug lisinopril 10 mg in the morning after waking up. As a result of the treatment, after 3 months the target BP levels were achieved, but SBP and DBP pattern have been transformed into «non-dipper» ones. The treatment regimen was modified: patient was recommended daily dose of lisinopril distributed into two doses-5mg in the morningand5mg in the evening before going to bed with the subsequent control by ABPM in 3 months.